BANK AIR SEBAGAI SOLUSI MENGATASI KELANGKAAN AIR BERSIH SAAT BANJIR MELANDA JAKARTA - Prasetya, Bagus Tri; Kurniawan, Edi; Arto, Angga Budi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Jakarta canât be separated from threat of floods and canhapen at any time. Many factor that cause flooding become issue, from the waste matter, poor water uptake, until settlements. Floods also resulted loss to the citizens. One of the worst loss is the scarcity of clean water after the flood. Ideas proposed in PKM-GT is to manufacture Water Bank. Itâs useful to overcome scarcity of clean water after flooding, with flood water will process into clean water, then itâs ready to be consumed. So people can get the clean water every day.